Dysregulated H3K27 Acetylation Is Implicated in Fatty Liver Hemorrhagic Syndrome in Chickens - Zhu, Yaling; Zeng, Qingjie; Li, Fang; Fang, Haoshu; Zhou, Zhimin; Jiang, Tao; Yin, Chao; Wei, Qing; Wang, Yujie; Ruan, Jiming; Huang, Jianzhen (Frontiers in Genetics, 2021)
Epigenetic regulation of gene expression has been reported in the pathogenesis of metabolic disorders such as diabetes and liver steatosis in humans. However, the molecular mechanisms of fatty liver hemorrhagic syndrome (FLHS) in chickens have been rarely studied. H3K27ac chromatin immunoprecipitation coupled with high-throughput sequencing and high-throughput RNA sequencing were performed to compare genome-wide H3K27ac profiles and transcriptomes of liver tissue between healthy and FLHS chickens. In total, 1,321 differential H3K27ac regions and 443 differentially expressed genes were identified (|log2Fold change| ≥ 1 and P-value ≤ 0.05) between the two groups. Binding motifs for transcription factors involved in immune processes and metabolic homeostasis were enriched among those differential H3K27ac regions. Differential H3K27ac peaks were associated with multiple known FLHS risk genes, involved in lipid and energy metabolism (PCK1, APOA1, ANGPTL4, and FABP1) and the immune system (FGF7, PDGFRA, KIT). Previous studies and our current results suggested that the HELP diet might have an impact on histone modification and chromatin structure, leading to the dysregulation of candidate genes and the PPAR signaling pathway, which causes excessive accumulation of fat in the liver tissue and induces the development of FLHS. These findings highlight that epigenetic modifications contribute to the regulation of gene expression and play a central regulatory role in FLHS. The PPAR signaling pathway and other genes implicated in FLHS are of great importance for the development of novel and specific therapies for FLHS-susceptible commercial laying hens.